2013
DOI: 10.1016/j.apmr.2013.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status Impairment Is Associated With Unplanned Readmissions

Abstract: Objective: To determine whether functional status on admission to a Comprehensive Integrated Inpatient Rehabilitation Program (CIIRP) is associated with unplanned readmission to acute care. Design: Retrospective cohort study. Setting: Academic hospital-based CIIRP. Participants: Consecutive patients (NZ1515) admitted to a CIIRP between January 2009 and June 2012. Interventions: Patients’ functional status, the primary exposure variable, was assessed using tertiles of the total FIM score at CIIRP admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 48 publications
3
73
3
2
Order By: Relevance
“…However, the authors concluded that their results, based on data from a single inpatient rehabilitation hospital, needed to be replicated in a nationally representative sample to better understand their findings, scope and generalizability. 22 Our study addresses this gap and corroborates their findings. The magnitude of our estimated effect is, however, lower than theirs (two times vs. three times difference in the odds of readmissions among patients with low and high scores).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, the authors concluded that their results, based on data from a single inpatient rehabilitation hospital, needed to be replicated in a nationally representative sample to better understand their findings, scope and generalizability. 22 Our study addresses this gap and corroborates their findings. The magnitude of our estimated effect is, however, lower than theirs (two times vs. three times difference in the odds of readmissions among patients with low and high scores).…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Hoyer and colleagues reported that Functional Independence Measures (FIM) (a standard measurement of function in inpatient rehabilitation facilities) motor domains were more highly related to unplanned readmissions than the cognitive domains. 22 Pearson and colleagues found similar results among chronically ill patients using the MOS 36-Item Short-Form Health Survey (SF-36). 33 However, other studies report that mental functioning also 19,41 Further research is needed to understand the interplay between physical and mental components and hospital readmissions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…10,23,29 However, in our sample, cognition at discharge exhibited a weaker association with rehospitalization than mobility or self-care. The low prevalence of cognitive dysfunction as measured by the cognitive Figure 1.…”
Section: Discussionmentioning
confidence: 38%
“…5 Previous studies examining rehospitalization and post-acute inpatient rehabilitation have focused on predictors other than the functional domains identified by the IMPACT Act and outcomes other than post-discharge 30-day unplanned rehospitalization. 9,11,[21][22][23][24][25][26] Unplanned rehospitalizations have the potential for improvement 7,27 and are the focus of the current quality improvement policies being developed by CMS and the National Quality Forum. 28 In our national sample of community-dwelling adults who were discharged from post-acute rehabilitation, the overall unadjusted 30-day unplanned rehospitalization rate was 12.0 %.…”
Section: Discussionmentioning
confidence: 99%